Economical Aspect of Heat Exchanger Cleaning Affected by Fouling - Mades Darul Khairansyah; Totok R. Biyanto (Institut Teknologi Sepuluh Nopember, 2015)
Fouling is the accumulation of foulant in a heat exchanger. Fouling increases the pressure drop and energy loss. Losses due to fouling in the distillation unit for crude oil reached US 4.2-10 billion per year in the United State. Fouling couldn’t be avoided, but it could be mitigation. One of the mitigation method is periodic cleaning of the heat exchanger. The time interval of a heat exchanger cleaning schedule is 1-36 months. Energy recovery, additional costs due to the performance of the pump and the cleaning cost are used as variables to determine saving. Results from this research showed that the heat exchanger is cleaned at 9 month is optimal cleaning schedule. Heat exchanger has savings about IDR 7.9 billion at 9 month. The amount is derived from the energy recovery about IDR 8.8 billion, reduced by a cleaning cost about IDR 0.2 billion and the advantage due to additional pumping cost about IDR 1.1 billion.